Black Phosphorus/Platinum Heterostructure: A Highly Efficient Photocatalyst for Solar‐Driven Chemical Reactions. Issue 40 (2nd September 2018) - Bai, Licheng; Wang, Xin; Tang, Shaobin; Kang, Yihong; Wang, Jiahong; Yu, Ying; Zhou, Zhang‐Kai; Ma, Chao; Zhang, Xue; Jiang, Jun; Chu, Paul K.; Yu, Xue‐Feng
Abstract: A 2D black phosphorus/platinum heterostructure (Pt/BP) is developed as a highly efficient photocatalyst for solar‐driven chemical reactions. The heterostructure, synthesized by depositing BP nanosheets with ultrasmall (≈1.1 nm) Pt nanoparticles, shows strong Pt–P interactions and excellent stability. The Pt/BP heterostructure exhibits obvious P‐type semiconducting characteristics and efficient absorption of solar energy extending into the infrared region. Furthermore, during light illumination, accelerated charge separation is observed from Pt/BP as manifested by the ultrafast electron migration (0.11 ps) detected by a femtosecond pump‐probe microscopic optical system as well as efficient electron accumulation on Pt revealed by in situ X‐ray photoelectron spectroscopy. These unique properties result in remarkable performance of Pt/BP in typical hydrogenation and oxidation reactions under simulated solar light illumination, and its efficiency is much higher than that of other common Pt catalysts and even much superior to that of conventional thermal catalysis. The 2D Pt/BP heterostructure has enormous potential in photochemical reactions involving solar light and the results of this study provide insights into the design of next‐generation high‐efficiency photocatalysts. Abstract : A 2D black phosphorus/platinum heterostructure (Pt/BP) is developed as a highly efficient photocatalyst. The Pt/BP exhibits a broad adsorption range (>1800 nm), ultrafast electron migration (0.11 ps), and efficient electron accumulation on Pt. These unique properties result in remarkable performance of Pt/BP in solar‐driven chemical reactions and the efficiency is superior to that of conventional thermal catalysis.